CRISIS OF PEDAGOGICAL CULTURE AND SOME PROBLEMS OF THE MODERN PEDAGOGICAL THOUGHT - R. M. Asadullin; O. V. Frolov (Образование и наука)
The evolution of content and forms of the dominating social relations caused the crisis of education; one of negative consequences of that crisis has become a gradual loss of the spiritual and moral bases of pedagogical culture. The possibilities of formation and realization of standards of behavior and work of teachers are discussed in the present publication based on culturological and axiological approaches to a phenomenon of this type of culture.The aim of the article is to determine the nature of the changes in the pedagogical culture of the teacher, reflected on the content of the theoretical and practical pedagogy.Methodology and research methods. The study is based on the philosophical-cultural analysis of the problems of formation and realization of pedagogical culture of norms in the context of the destabilization of modern axiological standards of professional teaching. We used the methods of theoretical research, including interdisciplinary analysis and synthesis of information from the philosophical, sociological, psychological and educational literature; empirical methods: the study of the experience of professional educational activities in a cultural context, questioning, interview.Results. The pedagogical culture of the teacher is characterized as the anthropomorphous practice which is putting forward a Person as the leading carrier of content of education and the main value. Research thesis on the declared range of problems of the Russian and foreign authors are presented. The changes in cultural practice and discursive formations in education are established; the difference of classical and modern understanding of pedagogical culture is stated. The role and value of pedagogical science in formation of a new view on essence of professional culture of the teacher in the conditions of crisis of the anthropocentric absolutes are considered.The authors set changes in cultural practices and discursive formations that distinguish the classical understanding of pedagogical culture of the modern. The role and importance of science teaching in the formation of a new look at the nature of a professional culture in the conditions of crisis anthropocentric absolutes.Scientific novelty. The concepts affecting the nature and content of modern pedagogical culture are theoretically proved. The primary tasks that face the modern pedagogical science and require operative decision are designated.Practical significance. According to authors of article, active development of the noted directions of a modern pedagogical thought will have a positive impact on the modern pedagogy and pedagogical culture of the teacher.